Egyptian-Israeli Relations after Operation Flood of Al-Aqsa (2023-2025): A Descriptive-Analytical Study of Political and Diplomatic Transformations - Alastal, Mohammed Haidar (Journal of Humanities & Social Sciences, 2025)
This study examines the nature of Egyptian-Israeli relations as one of the fundamental pillars of the regional security equation in the Middle East. It aims to analyze the trajectory of these relations during the period from 2023 to 2025 and anticipate the future of the Camp David Accords 1978 signed between the two sides, in light of the rapid field and political developments in the region, The researcher adopts a historical, descriptive, and analytical approach to trace the historical roots of Egyptian-Israeli relations and analyze their current reality in light of the repercussions of Operation Breaking Dawn 2023 launched by the Palestinian resistance in the Gaza Strip against Israel, and the subsequent complex political and security repercussions that affected both sides, The study’s timeframe extends from 2023 to 2025, a period that witnessed profound transformations in the nature of relations between the two sides, The geographical boundaries include the Arab Republic of Egypt, Israel, the Gaza Strip, and the Sinai Peninsula, as the main arena for security and political interactions between them. The objective boundaries focus on analyzing the course of bilateral relations between Egypt and Israel and anticipating the future of the Camp David Accords in light of rapid regional developments, The study concludes that Operation Protective Edge put the Camp David Accords to a true historical test; although they did not collapse, they lost much of their flexibility. The study also reveals that the bilateral relationship was characterized by intertwined interests and mutual concerns: Egypt seeks to protect its national security and the stability of its borders, while Israel seeks to maintain its strategic partnership with Cairo and avoid any direct military confrontation. The study also indicates that a partial truce scenario remains the most likely in the short term, with the possibility of limited escalation if red lines are crossed, Among the study’s most important recommendations are the need to support the Egyptian, Arab, and international position rejecting the displacement of Gaza’s population to the Sinai Peninsula.